Creative Thinking of Middle School Students in Solving Physics Problems - Septin Grahaning Tyas; Erman (Indonesian Journal of Science Learning (IJSL), 2021)
This study aims to describe the creativity in thinking of junior high school students in solving physics problems. Creativity in thinking is important for students to make themselves understand a physics concept, such as force, work, etc. Creativity in thinking is also needed so that students can find several possible problem solving according to their potential and are not fixated on a method because basically every student has their own imagination and thought process. Twelve students in the class VIII J of SMP Negeri 1 Jombang participated in the study. Data obtained from student’s thinking creativity test instrument which is strengthened by data from student and teacher interviews. Data analysis referred to three indicators of creativity used in the study: fluency, flexibility, and originality. The results showed that the students’ thinking fluency with high ability and some students with medium and low abilities got high scores. The highest score of the flexibility indicator was obtained by students with low abilities. High scores for the originality indicator were also obtained by several students from the high, medium, and low ability groups. High creativity scores are not only obtained by high-ability students but also medium, and low-ability students. The creativity of students’ thinking in solving physics problems is different. Students’ knowledge and experience play a role in the differences in students’ creativity in thinking fluently, flexible, and new. So that teachers can use learning methods that provide direct experience to students to make it easier for students to understand a concept and also improve students’ mathematical operational abilities to make it easier for them to solve a problem that requires mathematical calculations.